2002
DOI: 10.1177/019394502320555377
|View full text |Cite
|
Sign up to set email alerts
|

Older Latinos, Pets, and Health

Abstract: The majority of thefindings regarding pet ownership, interaction, and the human-animal bond have involved only Caucasians or have included other ethnic group members only incidentally. The extent to which older adultsfrom other ethnic groups may benefitfrom pet ownership and interaction is unclear. If the benefits of human-animal interaction are to be used effectively in promoting health and preventing illness, it is necessary to identify the "boundaries" of effectiveness for this interaction across various po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Several of the studies in our review provided evidence that dogs facilitate increased social interactions in a variety public spaces, including parks, sidewalks, and pathways, as well as public transit facilities, school drop-off areas, and outdoor malls [5-7,9,33,44,45,51-53]. The controlled experimental studies that measured quantity and quality of social interactions resulting from the presence of a dog confirmed that these were initiated by the 'other' as opposed to the dog-owner or the dog itself [51,52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the studies in our review provided evidence that dogs facilitate increased social interactions in a variety public spaces, including parks, sidewalks, and pathways, as well as public transit facilities, school drop-off areas, and outdoor malls [5-7,9,33,44,45,51-53]. The controlled experimental studies that measured quantity and quality of social interactions resulting from the presence of a dog confirmed that these were initiated by the 'other' as opposed to the dog-owner or the dog itself [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Women [4,34-39], ethnic minorities [34-40], and older adults [29,31,39] seemed to be most susceptible to experiencing other people's dogs as barriers to being physically active, although there were exceptions [45,50]. In contrast, studies focusing upon middle-class, predominantly Caucasian adult populations positioned other peoples' dogs as either having no impact on the physical activity patterns of women [58] or older adults [59], or as facilitators of physical activity through the positive contributions made to the social environment [5-7,9,33,41,54].…”
Section: Discussionmentioning
confidence: 99%
“…Further, NHW and Black dog owners were less likely to be sedentary ≥8 hr/day as compared to non-dog owners, but this relationship was not observed in Hispanics. Johnson and Meadows (Johnson and Meadows, 2002) found older Latino dog owners (50–83 years of age) view their dogs as valuable companions and family members similar to NHW. However, this perception was not associated with physical activity behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…24 Minority populations, who are most often at risk of physical inactivity, 1 would be a logical target population for dog walking interventions, especially given the findings of high attachment to their pets and indications that the dog-owner relationship is an important predictor of dog walking. 23,24 Interestingly, older participants were more likely to accumulate 30 minutes of dog walking in a oneday period than younger participants. This finding contrasts with other studies examining overall leisure-time physical activity prevalence.…”
Section: Discussionmentioning
confidence: 99%